Women in Microwaves: Linda Katehi - Marsh, Allison; Kuisel, Katherine (IEEE journal of microwaves, 2021)
This article is the first in a continuing series of biographical pieces on women who have made significant and continuous contributions to microwave science, technology, and applications over the course of their careers. Currently, women represent fewer than 7% of the members in the Microwave Theory and Technique Society (which hosts this journal). This series aims to correct that gender imbalance by highlighting the accomplishments of women and inspiring others to join their ranks. The articles are based on oral histories with the subject, conducted in conjunction with the IEEE History Center and deposited online with the Engineering and Technology History Wiki. The focus of this article is Dr. Linda Katehi, an IEEE Life Fellow, who is recognized for her contributions to phased array packaging and high-frequency characterization of novel feeding networks for printed antennas and arrays. She has spent her career in academia, including many years in university administration, but she has never been far from her research.